2015
DOI: 10.1371/journal.pone.0139624
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Preoperative Presence of Hydronephrosis and Flank Pain Independently Predicts Worse Outcome of Upper Tract Urothelial Carcinoma

Abstract: ObjectivesTo investigate the impact of preoperative hydronephrosis and flank pain on prognosis of patients with upper tract urothelial carcinoma.MethodsIn total, 472 patients with upper tract urothelial carcinoma managed by radical nephroureterectomy were included from Kaohsiung Medical University Hospital Healthcare System. Clinicopathological data were collected retrospectively for analysis. The significance of hydronephrosis, especially when combined with flank pain, and other relevant factors on overall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Flank pain in patients with UTUC is reported to be correlated with hydronephrosis, in that the sudden occurrence of hydronephrosis can result in intense pain in the flank area, while the gradual development of hydronephrosis generally cause dull pain with no attacks of renal colic [20]. Still it's notable that many asymptomatic patients had hydronephrosis, which possibly due to different sensations among patients.…”
Section: Discussionsupporting
confidence: 91%
“…Flank pain in patients with UTUC is reported to be correlated with hydronephrosis, in that the sudden occurrence of hydronephrosis can result in intense pain in the flank area, while the gradual development of hydronephrosis generally cause dull pain with no attacks of renal colic [20]. Still it's notable that many asymptomatic patients had hydronephrosis, which possibly due to different sensations among patients.…”
Section: Discussionsupporting
confidence: 91%
“…And it is noteworthy that preoperative hydronephrosis, a potential prognostic predictor discussed in some studies [23][24][25][26], was also found to be an independent predictor of survival. Additionally, we also investigated the association between preoperative pyuria and bladder recurrence following RNU (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 95%
“…Of the 14 studies, provided HR and % CI values directly; of the other 2 studies, one paper provided the relative risk (RR), and the other article provided OR values, which we used to estimate HR. Of the 14 studies, a significant association between preoperative hydronephrosis and poor CSS, OS, RFS or MFS was demonstrated in six (Chung et al, 2014;Liang et al, 2016;Ng et al, 2011;Yeh et al, 2015;Zhang et al, 2013;Zhang et al, 2015), four (Chapman et al, 2009;Liang et al, 2016;Yeh et al, 2015;Zhang et al, 2015), three (Chung et al, 2014;Hwang et al, 2013;Luo et al, 2013) or one (Ng et al, 2011) studies, respectively. Of the literature, the six (Bozzini et al, 2013;Sakano et al, 2013;Xing et al, 2016;Yeh et al, 2015;Zhang et al, 2016;Zou et al, 2014), two (Bozzini et al, 2013;Yeh et al, 2015), four (Chung et al, 2014;Liang et al, 2016;Luo et al, 2013;Ng et al, 2011) or three (Bozzini et al, 2013;Colin et al, 2014;Luo et al, 2013) studies linking preoperative hydronephrosis with poor CSS, OS, RFS or MFS, respectively, lacked statistical significance.…”
Section: Eligible Studies and Quality Assessmentmentioning
confidence: 99%
“…Initially, our search strategy identified 357 articles. A total of 19 studies published between 2007 and 2016 were included in the final meta-analysis (Bozzini et al, 2013;Chapman et al, 2009;Chen et al, 2013;Cho et al, 2007;Chung et al, 2014;Colin et al, 2014;Fradet et al, 2014;Hwang et al, 2013;Liang et al, 2016;Luo et al, 2013;Messer et al, 2013;Ng et al, 2011;Sakano et al, 2013;Xing et al, 2016;Yeh et al, 2015;Zhang et al, 2016;Zhang et al, 2013;Zhang et al, 2015;Zou et al, 2014) (Fig. 1).…”
Section: Eligible Studies and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation